Price Strategy Analysis, Marketing Public Relations, and Personal Selling on Purchasing Decisions with Brand Awareness as a Moderating Variable (Case Study at PT Rentokil Indonesia West Region Marketing Area) - Tristi Iriana (Budapest International Research and Critics University, 2023)
This study aims to empirically examine the effect of price on purchasing decisions, the effect of marketing public relations on purchasing decisions, the influence of personal selling on purchasing decisions, the effect of price, marketing public relations, and personal selling moderated by brand awareness on purchasing decisions. This analysis uses independent variables, namely price, marketing public relations, and personal selling. The dependent variable is the purchase decision, while the moderating variable is brand awareness. The sample was conducted by purposive sampling method. The data was collected using questionnaires which were distributed directly to respondents, totaling 100 customers of PT Rentokil. Statistical method using Moderating Regression Analysis, with statistical test hypothesis testing t. The results of this study indicate that the effect of price on purchasing decisions has an insignificant result, which means it has no effect. While the influence of marketing public relations on purchasing decisions, the influence of personal selling on purchasing decisions, the influence of prices, marketing public relations, and personal selling moderated by brand awareness on purchasing decisions have significant results and have a direct influence on the dependent variables.